Epidemiology of Haemophilus somnus infection in dairy cattle in Quebec. - Sanfaçon, D (1983)
Serological studies on Haemophilus somnus infection were carried out on 1795 cattle from 231 dairy herds in the province of Quebec. An epidemiological investigation was done in each of the dairy operations. Seroreactivity rate and mean log2 titer for all the sera were 55.4% and 4.1620 respectively. Cattle from eastern regions of Quebec demonstrated the lowest prevalence of H. somnus agglutinins. The percentage of seroreactor animals was 60.3 in herds of 100 cattle or more in comparison to 53.2 in herds of smaller size. About 75% of the animals from 16 herds in which one or more cattle showed nervous manifestations of undetermined origin over a one year period had antibodies to H. somnus. Herds in which respiratory diseases occurred had 59.6% seroreactor animals and herds in which weak calf syndrome was diagnosed over a one year period had 61.4% seroreactor animals. In 87 herds located within 20 km of feedlots, 61.8% of the sera had titers and the mean log2 titer was 4.4813.